Advanced Methods for Inconsistent Knowledge Management - Nguyen, Ngoc Thanh (Advanced Information and Knowledge Processing, 2008)
Inconsistent knowledge management is a common sub-field of knowledge management and conflict resolution. It deals with methods for reconciling inconsistent contents of knowledge originating from different sources. This book presents a unified and systematic description of a wide class of miscellaneous problems of inconsistent knowledge management, analyzed by traditional mathematical methods using relational and logical representations. With special emphasis on the distribution aspect of knowledge inconsistency, Professor Nguyen provides a unique approach to formal models of inconsistency and algorithms for its resolution. Features & topics include: • Consensus as a tool for conflict solving • Inconsistency of knowledge - syntactic & semantic • Knowledge conflict model • Ontology Integration • Practical aspects of applications of proposed methods This book provides a broad snapshot of intelligent technologies for inconsistency resolution and offers an invaluable source of reference on the topic. Written for researchers and students in the field of knowledge management, conflict solution and intelligent systems, this book will also be of use to designers of multi-agent and information systems and specialists from social choice theory, and all interested in the problems of processing and managing inconsistent knowledge.